Pendidikan Kesehatan Pemilihan Aktivitas Yang Tepat Pada Penderita Gout Di Puskesmas Polokarto - Saputro, Wisnu, Supratman, Ph.D (2016)
Uric acid or gout is a disease of the joints caused by the uric acid content is entered and stored in the joints whose levels exceed the normal limits.The family is the smallest unit of society consisting of the head of the family and some people gathered and stay somewhere under a roof in a state of dependency. Based on the survey WHO , Indonesia is the fourth largest country in the world whose inhabitants suffer from gout and based on the source of the Bulletin of Natural , in Indonesia 35 % of gout in men under 34 years old . Based on data from the authors take the title the title "Health Education Activity Award Selection of the Right in Nursing Family TN.R With Gout in Mranggen Village , District Polokarto , Sukoharjo. " There are two nursing diagnoses while appropriate for Ny . SS is the Family Physical Mobility Disorders associated with inability to Caring Family Ny.SS with Gout and pain associated with the inability to Know Your Family Health Problems Gout . The action taken by the authors do discuss activities with the family about how to care with the family about how to care with mobility impairments family . Stop the intervention associated with the inability of the family to care for family members who suffer from gout